PENGARUH SENAM YOGA DAN KOMPRES HANGAT TERHADAP TINGKAT NYERI DISMENORE PADA REMAJA PUTRI DI SMPN 02 KOTA BENGKULU - Shovina, Dian Shovina; Darwis, Darwis; Yulyana, Nispi (JURNAL BESUREK JIDAN, 2024)
Dysmenorrhoea is a common problem for women worldwide. Worldwide, the prevalence of dysmenorrhoea cases is 90% (1,769,425 people). Non-pharmacological treatments for dysmenorrhoea include yoga exercises and warm compresses. The purpose of the study was to determine the effect of yoga exercises and warm compresses on the pain level of dysmenorrhoea of adolescent girls studying at SMPN 02 Bengkulu City in 2024. The study was a quasy experiment with pre-test and post-test design involving two groups. The sample consisted of 40 people, consisting of 20 yoga exercises and 20 warm compresses. Purposive sampling technique was used to collect the sample. Wilcoxon and Mann Whitney tests were used to analyse the data. The results showed that there was an effect of yoga exercises (pvalue 0.000) and warm compresses (pvalue 0.000) on the level of dysmenorrhoea pain with a mean difference in yoga exercises (1.30) and warm compresses (2.15). The Mann-Whitney test results show that yoga exercises are less effective than warm compresses (0.65) in reducing dysmenorrhoea. Yoga exercises and warm compresses are expected to reduce dysmenorrhoea. However, warm compress is the best way to reduce pain that is immediately felt when the intervention is carried out.